Building Integrated Photovoltaic Thermoelectric Wall System: Balancing Simulation Speed and Accuracy. (May 2017) - Luo, Yongqiang; Zhang, Ling; Liu, Zhongbing; Wu, Jing; Wang, Xiliang; Xie, Lei; Xu, Xiu; Lv, Xiaohui
Abstract: A proper parameters setting is crucial to both simulation speed and accuracy. This is particularly true for the simulation of complicated systems. Building integrated photovoltaic thermoelectric wall system (BIPVTE) is an effective and innovative active building envelope system which can largely cut building energy consumption. The basic thermal model of BIPVTE wall system was established and two important model parameters were optimized to provide useful guide for further investigation of this active wall system. The numerical study in terms of time step Δ h and superposition number N in model integral calculation were conducted and analyzed to balance simulation speed and accuracy. It is concluded that time step should be set around 10 min to 30 min and parameter N around 6 to 8 for the annual thermal performance simulation of BIPVTE wall system. But if the simulation task is typical day calculation, time step should be set as around 1 min.